In-vitro digestibility and functionality of heated and defatted oilseed flours - Muhammad Ashraf Chaudry,; Nizakat Bibi,; Amal Badshah,; M. Jamil Qureshi, (Universiti Kebangsaan Malaysia, 2003)
Defatted oilseed protein flours of soybean (DSYF), rapeseed (DRF), sunflower (DSF) and peanut (DPF) were heated in an electric oven at 100oC for 5 and 10 minutes. Maximum nitrogen solubility (NS) was recorded in DPF (72%). The NS was decreased as a result of heat treatment in case of DRF and DSF. The in-vitro digestibility (IVD) decreased in DPF and no effect was found on IVD of DSYF samples. In case of DSF samples increase in IVD was more at 5 minutes treatment than that of 10 minutes treatment. Maximum foaming capacity (FC) was observed in DSF (66.5 ml/g) and minimum in DRF (56.0 ml/g) in unheated samples. No effect of heat treatment was found on FC of DRF samples and FC increased in case of DSF samples. In case of DRF, very little effect was noted on FC. Heat treatment had an overall increasing effect on oil absorption, however, more reduction in oil absorption capacity was found in DSF and DPF than DRF and DSYF. It was concluded that certain functional properties can be enhanced by heat treatment while others can be decreased which might be beneficial for specific product formulation.